Brain-Derived Neurotrophic Factor Elevates Activating Transcription Factor 4 (ATF4) in Neurons and Promotes ATF4-Dependent Induction of Sesn2 - Liu, Jin; Amar, Fatou; Corona, Carlo; So, Raphaella W. L.; Andrews, Stuart J.; Nagy, Peter L.; Shelanski, Michael L.; Greene, Lloyd A. (Frontiers in Molecular Neuroscience, 2018)
Activating transcription factor 4 (ATF4) plays important physiologic roles in the brain including regulation of learning and memory as well as neuronal survival and death. Yet, outside of translational regulation by the eIF2α-dependent stress response pathway, there is little information about how its levels are controlled in neurons. Here, we show that brain-derived neurotrophic factor (BDNF) promotes a rapid and sustained increase in neuronal ATF4 transcripts and protein levels. This increase is dependent on tropomyosin receptor kinase (TrkB) signaling, but independent of levels of phosphorylated eIF2α. The elevation in ATF4 protein occurs both in nuclei and processes. Transcriptome analysis revealed that ATF4 mediates BDNF-promoted induction of Sesn2 which encodes Sestrin2, a protector against oxidative and genotoxic stresses and a mTor complex 1 inhibitor. In contrast, BDNF-elevated ATF4 did not affect expression of a number of other known ATF4 targets including several with pro-apoptotic activity. The capacity of BDNF to elevate neuronal ATF4 may thus represent a means to maintain this transcription factor at levels that provide neuroprotection and optimal brain function without risk of triggering neurodegeneration.